The relationship between metacognitive monitoring, non-verbal intellectual ability, and memory performance in kindergarten children - Kolloff, Kristin; Roebers, Claudia M. (Frontiers in Developmental Psychology, 2024)
When assessing their certainty, children are often poor at accurately monitoring their level of learning. The study examined the relationships between memory performance, intellectual ability, and metacognitive monitoring accuracy in kindergarten children. We also explored whether specific thresholds in memory performance and nonverbal intellectual ability influence metacognitive monitoring accuracy to identify group-specific patterns that might be masked by an overall linear analysis. We assessed the monitoring discrimination of 290 kindergarteners (Mage 6 years) using a paired-associates learning task. Results showed small correlations between task performance, intellectual ability, and metacognitive monitoring. Nonverbal intellectual ability provided explanatory value for monitoring accuracy beyond memory performance. We observed groupspecific results consistent with the unskilled-and-unaware effect; children with the highest memory skills were more effective at discriminating between correct and incorrect answers than their peers with the lowest memory skills. However, kindergarteners with the highest nonverbal intellectual abilities did not demonstrate greater cognitive adaptability in novel tasks, as their monitoring accuracy was comparable to that of peers with average or lower intellectual abilities. Findings indicate that both task performance and nonverbal intellectual ability are relevant for monitoring accuracy, but the impact of nonverbal intellectual ability was less significant than anticipated. The modest correlation suggests that kindergarteners' nonverbal intellectual ability and metacognitive monitoring abilities operate relatively independently.